A new record of deep-sea shrimp Glyphocrangon investigatoris Wood-Mason & Alcock, 1891 (Decapoda: Glyphocrangonidae) from the southeastern Arabian Sea - Kuberan, G.; Chakraborty, Rekha Devi; Purushothaman, P.; Maheswarudu, G.; Sreesanth, L.; Ragesh, N. (Zootaxa, 2019)
Here, we report the new record of deep-sea caridean shrimp Glyphocrangon investigatoris Wood-Mason & Alcock, 1891 from the Arabian Sea along the Indian coast. The three individual specimens were collected from Sakthikulangara fish landing center (fishing off Kollam 8°56’60.78”N/76°32’34.27”E) obtained from deep-sea bottom trawlers between 200 and 300 m depth along the southwest coast of India in December of 2017 and the voucher specimen was deposited to the Marine Biodiversity Referral Museum at Central Marine Fisheries Research Institute. The species of G. investigatoris is considered as one of the data deficient in distributional range, which was only recorded from northern and southern Bay of Bengal. The intraspecies genetic distance in the COI gene of G. investigatoris retrieved from NCBI revealed 0.6–0.7% while interspecies distance ranged from 5% to 26.5% and 16S was found between 1.1% to 8.1% and the closest genetic distance ranged with G. regalis.